Between Reprimands and Support: An Exploration of Politeness in Teacher-Student Interaction in the Classroom Environment - Suroso, Eko (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
Communication issues between educators and students in classroom management pose challenges, especially when balancing motivation and discipline. This study aims to investigate patterns of teacher reprimand and supportive communication in classroom interactions simultaneously and understand how communication dynamics affect student learning. A qualitative design with a descriptive approach involved teachers and students in the research project across three secondary schools in Purbalingga, meeting diverse classroom criteria. Data collection methods included documentation, field notes, direct observation, and interviews organized during the academic year of the three-phase systematic research. Thematic analysis was used to examine the data. Results showed that the proportional ratio between reprimand and support depended on class characteristics. Thus, disciplined classes showed a ratio of 1:2; conducive streams were closer to 1:1.5, and even "less controlled" conducive classes relied on reprimands (1:1.5). Direct reprimands proved more effective in crises, while verbal support increased student motivation, especially for students with low participation. Regression analysis revealed a significant positive correlation of 0.6 between support and student motivation and a weak negative correlation of -0.3 for reprimands. Thus, teacher training based on these abilities is indispensable in educational practice.